2012
DOI: 10.1136/bmjopen-2012-000992
|View full text |Cite
|
Sign up to set email alerts
|

Candida parapsilosiscandidaemia in a neonatal unit over 7 years: a case series study

Abstract: ObjectiveTo evaluate Candida parapsilosis candidaemia in a neonatal unit over 7 years.DesignCase series study.SettingA 2000-bed tertiary-care university hospital at São Paulo, Brazil.ParticipantsNeonates hospitalised in a 63-bed neonatal unit.Primary and secondary outcome measuresWe evaluated the incidence of C parapsilosis fungemia in a neonatal unit from 2002 through 2008 and the main microbiological, clinical and epidemiological aspects of this disease in neonates. During the study period an outbreak occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
1
15
0
2
Order By: Relevance
“…(1,20) The study showed bacterial sepsis to have a significant association with candidaemia in VLBW infants and is consistent with results in similar studies. (1,5,15) At the time of the study, the empiric antibiotics for late onset bacterial sepsis were meropenem and vancomycin. Fu et al demonstrated a strong association between carbapenem use and development of candidaemia.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…(1,20) The study showed bacterial sepsis to have a significant association with candidaemia in VLBW infants and is consistent with results in similar studies. (1,5,15) At the time of the study, the empiric antibiotics for late onset bacterial sepsis were meropenem and vancomycin. Fu et al demonstrated a strong association between carbapenem use and development of candidaemia.…”
Section: Discussionsupporting
confidence: 89%
“…(23,24) However, due to the lack of information in our database, these two risk factors were not included in the present study. (1,6,13,16,25,26) The increase in resistance to azoles by NAC is well demonstrated in this study with 41.2% of isolates of C. (28,29) The unit where the study was conducted, Amphotericin B was used to treat C. glabrata candidaemia.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This organism is the main Candida species responsible for a significant proportion of outbreaks of nosocomial fungaemia, particularly in neonate intensive care units (NICUs)131415161718. However, there are limited studies exclusively assessing the epidemiology of candidaemia caused by C. parapsilosis in China, and no description of C. parapsilosis clustering or outbreak cases has been reported to date19.…”
mentioning
confidence: 99%
“…Candida epidemiyolojisindeki değişikliğin başlıca nedeni fl ukonazol kullanımındaki artış olarak bildirilmektedir 1,4,20,21 . Candida epidemiyolojisinde değişiklikler, C.albicans dışı kandidemi oranlarının, özellikle C.parapsilosis insidansının arttığını göstermektedir 22,23 . Bu çalışmada pediatri yoğun bakım üniteleri (YBÜ)'nde en sık, erişkin YBÜ'nde ise ikinci sıklıkla izole edilen türün C.parapsilosis olduğu görülmüştür.…”
Section: Gereç Ve Yöntemunclassified